Distorted Unbalanced Grid Voltage Modulated Direct Power Control for Three-Phase Grid-Connected Inverters - Yi-Hung Liao; Meng-Hsuan Yu; Hao-Min Zhang (IEEE Open Journal of Power Electronics)
In this paper, a linearized direct power control strategy for grid-connected inverters under distorted unbalanced grid voltage is proposed. The grid-connected inverters usually suffer from distorted unbalanced grid condition, which causes output active and reactive powers with oscillations and leads the three phase output currents with distortion. Although the conventional grid-voltage-modulated linearized direct power control was constructed in existing literature, it only considers and suitably applies to balanced grid voltage and makes significant power ripples and total harmonic current distortion (THDi) under non-ideal grid condition. In the presence of distorted and unbalanced grids, a direct power control strategy based on the extended power theory and symmetrical components theory considering positive and negative sequence components in the stationary reference frame without phase-locked loop (PLL) is proposed in this paper. The proposed strategy decouples the terms between unbalanced grid-side voltage and converter-side voltage, and transfers the original unbalanced three-phase nonlinear time-varying active and reactive power system into a linear time-invariant system, thereby simplifying the controller and calculation complexity. Furthermore, a ripple compensation method for LCL filter is also proposed to reduce the power ripple. Finally, the effectiveness and correctness of the proposed method are verified through some simulation and the practical implementation of a 1.5 kW inverter.